Analisis Hadis Tentang Keistimewaan Meninggal Pada Hari Jumat - Muhammad, Muhammad; Hidayat, Muhammad; Lubis, Saidah Elviah (UIN Sumatera Utara Medan, 2023)
This article discusses Friday is a glorious day, many hadith editors explain the special features of Friday, these traditions relate to orders to increase worship. On the other hand, there is a hadith which explains the privileges of Friday relating to death. This hadith explains the privilege of a Muslim who dies on Friday or Friday night will be free from the slander of the grave. This research method is included in the category of qualitative methods, by conducting source searches or library research, and using the maudu'i method, namely collecting hadiths that are meaningful with the traditions of the privilege of dying on Friday. and deviate both from the verses of the Koran and other hadiths. From the research process using the takhrij method, the hadith narrated by Imam Tirmizi, from the perspective of the sanad, is considered dhaif, but there is a history of Imam Ahmad who is a supporter, thus elevating the degree of the hadith to hasan lighairihi. Because the hadith has the status of hasan lighairihi, then the hadith is the same as the authentic hadith. Thus the hadith can be accepted and understood as a message to always ask Allah to die in a state of husnul khatimah, one of which is by dying on Friday